2009
DOI: 10.1007/s10971-009-2112-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and magnetic properties of nanocomposite Ni1−x Co x Fe2O4–BaTiO3 fibers by organic gel-thermal decomposition process

Abstract: Nanocomposites of ferrite and ferroelectric phases are attractive functional ceramic materials. In this work, the nanocomposite Ni 1-x Co x Fe 2 O 4 -BaTiO 3 (x = 0.2, 0.3, 0.4, 0.5) fibers with fine diameters of 3 * 7 lm and high aspect ratios were synthesized by the organic gelthermal decomposition process from the raw materials of citric acid and metal salts. The structure, thermal decomposition process and morphologies of the gel precursors and the resultant fibers derived from thermal decomposition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…When the calcination temperature is above 950 C, the grain size may be larger than the single-domain size and become into multidomains, and the formation of domain walls will cause the coercivity to decrease. 3 The M s value at 77 K is larger than the value at room temperature (seen Table II), which can be explained referring Bloch's law expressed as…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…When the calcination temperature is above 950 C, the grain size may be larger than the single-domain size and become into multidomains, and the formation of domain walls will cause the coercivity to decrease. 3 The M s value at 77 K is larger than the value at room temperature (seen Table II), which can be explained referring Bloch's law expressed as…”
Section: Resultsmentioning
confidence: 96%
“…[1][2][3] However, with the technology development, the pure M-type ferrite was difficult to meet the requirements. 4 In order to tailor the magnetic property and ferromagnetic resonant frequency to meet different requirements in different applications, various substitutions such as La 3+ , 5 Cr 3+ , 6 Sm 3+ , 7 La-Zn, 4 Co-Ti 8 were investigated based on the fact that the magnetic property is closely sensitive to the chemical composition, microstructure and the arrangement of ions in the crystal unit.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most common used magnetic materials are magnetite-lead ferrite, [58,59] garnet-type ferrite, [60] spinel-type ferrite [61] and perovskite ferrite. [61] Shen et al [63] reported SrFe 12 O 19 magnetite lead NFs fabricated by sol-gel assisted electrospinning and calcination process. The obtained NFs have a diameter of about 100 nm on average.…”
Section: Ferrite Based Magnetic Nanofibersmentioning
confidence: 99%
“…Thermal decomposition of precursors is one of the synthesis methods extensively used for the obtaining of nanoscaled ferrites and their composites, like ferrite/silica nanocomposites [14][15][16]. Our synthesis method for ferrites is based on the thermal decomposition of the mixed oxides precursor (carboxylate compounds of the involved metal ions) resulted in the redox reaction between a polyol and the mixture of metal nitrates [17].…”
Section: Introductionmentioning
confidence: 99%